The Authentication of the Past: Narrative Representations of History in the Gospel of John. (September 2020) - Luther, Susanne
Narrative historiography in John's gospel operates with a number of literary strategies, such as historical referentiality and eyewitness testimony, which serve to authenticate the narrative and to inscribe the (hi)story of Jesus into ancient history. At the same time, these authentication strategies are counteracted or 'ruptured' (for example, by strategies of ﬁctional literature), which situate John's narrative of this-worldly history within a symbolic, metahistorical framework; yet these strategies are not to be perceived as detrimental to the reception of the text as a factual text. This article discusses two narrative strategies through which referentiality and authenticity are created as well as counteracted in the Johannine text; it also describes the forms and functions of these literary strategies that support the christological conception of history in John's gospel.